2011
DOI: 10.3329/jhpn.v29i1.7562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of HIV/AIDS-infected Patients Admitted to a New Specialist Unit in Dhaka, Bangladesh - A Low-prevalence Country for HIV

Abstract: This paper describes the clinical features of a series of patients admitted to the specialist HIV/AIDS unit (Jagori) of the Dhaka Hospital, ICDDR, B (International Centre for Diarrhoeal Disease Research, Bangladesh) during May 2008–February 2010. Data were collected from a review of documents and electronic case-records and collation of laboratory results with respect to CD4 counts. One hundred and nine patients were admitted during this period. Their mean age was 33.4 years, and 62% were male. On admission, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…It shows that intravenous drug using can be one of the main transmission sources of HIV infection in adults. This result was in compatible with other studies of Iran: 55% in the study by Ramezani et al [] 78% in Ghannad et al study [Ghannad et al, ], and in contrast to other studies in Saudi Arabia (0.8%) [Madani et al, ] and Bangladesh (10%) [Matin et al, ].…”
Section: Discussionsupporting
confidence: 92%
“…It shows that intravenous drug using can be one of the main transmission sources of HIV infection in adults. This result was in compatible with other studies of Iran: 55% in the study by Ramezani et al [] 78% in Ghannad et al study [Ghannad et al, ], and in contrast to other studies in Saudi Arabia (0.8%) [Madani et al, ] and Bangladesh (10%) [Matin et al, ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of adult HIV was around 31 % in 2009 in India as per NACO fact sheets of March 2012 [1] and is showing a declining trend. A study from Bangladesh, a low prevalence country having <1 % prevalence, reported 109 admissions in a tertiary care specialized hospital during a 5-year study [3]. They quoted that around 7500 patients are living with HIV/ AIDS in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…With increase in the number of people living with HIV AIDS, intervention for known surgical problems was often required and new surgical problems hitherto less reported in the literature were also observed. Even though literature on HIV/AIDS is abundant, there is paucity of information with respect to surgical diseases encountered in the Indian subcontinent and are mainly related to specific problems [3]. Hence, this study was taken up to know the clinical spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of HIV in Bangladesh is often delayed for a variety of reasons, including lack of awareness of HIV infection due to its low prevalence, the limited number of HIV testing and counseling facilities, which is often a critical entry point for engagement into care and prevention, and the unwillingness of many people to be tested [7] , [8] . As a result, HIV infected persons are diagnosed in late stages of the disease and most hospitalized patients with HIV have a CD4 count of <200 cells/mm 3 [9] . The Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) opened the Jagori Ward, an inpatient unit for the management and treatment of people living with HIV (PLHIV), in May 2008.…”
Section: Introductionmentioning
confidence: 99%